Effectiveness of fidelity simulation based learning in primary medical care practicum course among nursing students - Thangkratok, Pramote; Palacheewa, Natchaya; Tongtham, Arbkhanok; Dechakul, Manida; Kaewprasong, Anongnat; Madsong, Chalermkwan (Thai Journal of Nursing, 2022)
This evaluation research aimed to evaluate effectiveness of fidelity simulation based learning in primary medical care practicum course in nursing students. The sample of 203 nursing students at Srisavarindhira Thai Red Cross Institute of Nursing, was purposively selected. The research instruments included, 1) a desirable characteristics assessment, 2) a knowledge test on primary medical care, and 3) a questionnaire on opinion toward learning experience. Data were analyzed using descriptive statistics, paired t-test, and content analysis. The findings showed that after the implementation of fidelity simulation based learning in primary medical care practicum course, nursing students’ desirable characteristics were at the high level (M = 3.86, SD = 0.20). They expressed their learning experience as positive experience, and need for real situation practice. At the end of this course learning, theirs knowledge on primary medical care was significantly higher than before the course learning at p < .001 ( t = -19.56).